Effect of Giving Organic Waste-Based Poc To The Growth of Kailan Plants (Brassica Oleracea L) - Yeni Ika Pratiwi; Nurul Huda; Eko Wahono (Faculty of Agriculture, Merdeka University Surabaya, Indonesia, 2022)
This study combined the use of variable doses of liquid organic fertilizers made from organic waste, wich a Factorial experimental study that uses a Randomized Group Design (RAK) consisting of 2 treatment factors. Factor I treatment is a type of POC raw material consisting of 7 levels: P0= Comparison without the provision of liquid organic fertilizer, but given basic fertilizer; P1= Given POC made from a mixture of materials 2 to 7; P2=Given POC made from vegetable waste (tomatoes and mustard); P3= Given POC made from waste fruits (bananas and papaya); P4= Given POC made from germinated waste; P5= Given POC made from waste food catering; P6= Given POC made from catfish waste; P7= Given POC made from animal slaughterhouse waste (cow's blood). The treatment of Factor II is the concentration of POC giving includes 3 levels, namely: K1= POC concentration of 4%=40 ml/ liter of solution; K2= POC concentration of 8%=80 ml/liter solution; K3= POC concentration of 12%=120 ml/liter of solution. The parameters of observations made on kailan plants include: the number and length of the plant. By comparing the concentration treatment of K1, K2 and K3 mentioned above, the K2 treatment (concentration of 8% POC) exerts a better influence than the treatment of K1 and K3, although it is not real from the K3 treatment. This shows that the use of POC made from organic waste with a concentration of 8% POC provides a significant influence that can play a role in increasing soil fertility and plant productivity.